Happy-Productive worker thesis: The role of work characteristics, gender, and age - Jaime A. Bayona; William F. Durán; Jesús Perdomo-Ortiz; Delio I. Castañeda; Carlos A. Valencia; Pauline Fatien Diochon; Diego F. Alvarado (PLoS ONE, 2025)
Happy-productive worker thesis (HPWT) research predicts four configurations depending on well-being and performance levels, one synergistic and three antagonists; however, there has been some discrepancy in the expected results of HPWT, as there are some inclusive results about the specific characteristics that lead to each one of the predicted groups. In this study, we face these discrepancies using a three-configuration model that is more realistic in the organizational context, and exploring how work characteristics, gender, and age can predict workers’ membership in such configurations. We performed multinomial logistic regressions using a sample of 504 Colombian workers and their supervisors from different economic sectors. The results indicated that different work characteristics are associated with the membership of workers in each group, and how this membership varies depending on gender and age group. Our findings offer new research and practice insights about the role of HPWT in HRM (human resources management).